Tenebrio molitor meal in diets for Nile tilapia juveniles reared in biofloc system - Tubin J.S.B.* (2020)
© 2019 Elsevier B.V.Different inclusion levels of mealworm meal Tenebrio molitor (TM) were investigated in diets for tilapia (Oreochromis niloticus) reared in biofloc systems. Five treatments were evaluated (0% or control, 5, 10, 15 and 20% of TM inclusion), with three replicates per treatment and 10 fish (2.08 ± 0.19 g) stocked per experimental unit. After six weeks, data was submitted to a regression analysis up to the second order. Zootechnical, somatic, hematological and biochemical parameters, as well as water quality, proximate composition of carcass and biofloc, abundance of the planktonic community and fatty acid profile of TM were analyzed and monitored. Throughout the experiment water quality parameters were kept within the required levels suited to this species. After six weeks, the final weight, weight gain, SGR, FCR, erythrocytes, hepatosomatic index and carcass composition (dry matter and ether extract) resulted in a linear effect when inclusion levels increased. Polynomial models and Plateau Linear Responses (LRP) were applied to survival and productivity (kg m−3) indicating maximum values of 11.68% and 10.68% of TM inclusion, respectively. Diverse groups of microorganisms were identified with a prevalence of protozoans, microalgae, diatoms and rotifers. Fatty acid (FA) profile of TM indicated high levels of saturated FA and moderate levels of linoleic and eicosapentaenoic FA. The overall results indicated that it is possible to include TM up to 10% in diets for tilapia juveniles raised in biofloc systems.